Environment induced self-aggregation behavior of κ-carrageenan/lysozyme complex. Issue 2 (October 2015) - Xu, Wei; Jin, Weiping; Zhang, Chunlan; Liang, Hongshan; Shah, Bakht Ramin; Li, Bin
Abstract: Self-aggregation behaviors of κ-carrageenan/lysozyme (CRG/Ly) complex inducing by intrinsic and extrinsic factors were investigated form macro and micro aspects, including the ratio, pH, temperature and salt. High Ly content promote aggregation behavior of CRG/Ly complex, while CRG played a suppressive role. Except for CRY5, the complex displayed nano-size distribution. Both CRG addition and the self-aggregation behavior could enhance the thermal stability of Ly. Low ζ-potential induced by pH made the CRG/Ly complex easy to self-aggregate into structure with large size due to the gradual association of complex to form lager interpolymeric complexes. The tunable process means to control the dissociation and association behavior between interpolymeric complexes and soluble complex by pH. All systems shared high NaCl tolerance and presented stable transmittance. Heat-induced self-aggregation exhibited a temperature and polymers ratios dependant manner. The mechanisms of environment induced self-aggregation into interpolymeric complexes reflected the re-balanced physical interaction when they suffered from any treatment. Controlling and regulating self-aggregation behavior of protein/polysaccharide system could enrich the soft structures from food respective and also provide practical theory for food process.